Peningkatan Ekonomi Kreatif dalam Pemanfaatan BUMDes Melalui Pelatihan Penyusunan Laporan Keuangan Sederhana di Desa Cinta Mulya Kecamatan Sidomulyo, Lampung Selatan - Dedi Putra; Anik Irawati; Pebrina Swissia; M. Ariza Eka Yusndera; Novi Hariyadi Sudibyo (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of this service activity is to help village officials, in this case BUMDes, to study government regulations regarding the budget and the use of village fund funding allocations. So that village officials understand government rules regarding the allocation of use and sources of funds to be used by the village. And this activity also helps MSMEs to learn to promote their business services/products through marketing content with attractive designs and using web content as their promotional media. It is hoped that this activity will be a positive contribution to Cinta Mulya village, especially village officials and MSME actors in carrying out their functions and roles in managing internal and state-owned finance.